2014
DOI: 10.1042/cs20140047
|View full text |Cite
|
Sign up to set email alerts
|

Targeting mitochondrial 18 kDa translocator protein (TSPO) regulates macrophage cholesterol efflux and lipid phenotype

Abstract: The aim of the present study was to establish mitochondrial cholesterol trafficking 18 kDa translocator protein (TSPO) as a potential therapeutic target, capable of increasing macrophage cholesterol efflux to (apo)lipoprotein acceptors. Expression and activity of TSPO in human (THP-1) macrophages were manipulated genetically and by the use of selective TSPO ligands. Cellular responses were analysed by quantitative PCR (Q-PCR), immunoblotting and radiolabelling, including [3H]cholesterol efflux to (apo)lipoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 44 publications
0
51
1
Order By: Relevance
“…In both global and conditional Tspo knock-out studies, several genes involved in steroidogenic processes were found to be upregulated including Cyp21a2 (110), Abca2 (110), and Scarb1 (111) in the adrenal glands and Lhcgr (111) in the testes ( TSPO is also attributed to immune regulation, with elevated expression observed in microglia and macrophages. Recently it was highlighted that TSPO is involved in cholesterol trafficking in macrophages, since its overexpression leads to increased transcription of proteins involved in cholesterol efflux, ACBA1 (ATP-binding cassette A1), PPARα (peroxisome-proliferator-activated receptor α) and LXRα (liver X receptor α), and corresponds with increased efflux of cholesterol to acceptors (113). This pathway is activated upon a moderate cholesterol load stress and it is proposed as a protective mechanism to reduce macrophage cholesterol mass (113).…”
Section: Tspo -/-Knockout Mice: New Insights Of An Old Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both global and conditional Tspo knock-out studies, several genes involved in steroidogenic processes were found to be upregulated including Cyp21a2 (110), Abca2 (110), and Scarb1 (111) in the adrenal glands and Lhcgr (111) in the testes ( TSPO is also attributed to immune regulation, with elevated expression observed in microglia and macrophages. Recently it was highlighted that TSPO is involved in cholesterol trafficking in macrophages, since its overexpression leads to increased transcription of proteins involved in cholesterol efflux, ACBA1 (ATP-binding cassette A1), PPARα (peroxisome-proliferator-activated receptor α) and LXRα (liver X receptor α), and corresponds with increased efflux of cholesterol to acceptors (113). This pathway is activated upon a moderate cholesterol load stress and it is proposed as a protective mechanism to reduce macrophage cholesterol mass (113).…”
Section: Tspo -/-Knockout Mice: New Insights Of An Old Functionmentioning
confidence: 99%
“…Recently it was highlighted that TSPO is involved in cholesterol trafficking in macrophages, since its overexpression leads to increased transcription of proteins involved in cholesterol efflux, ACBA1 (ATP-binding cassette A1), PPARα (peroxisome-proliferator-activated receptor α) and LXRα (liver X receptor α), and corresponds with increased efflux of cholesterol to acceptors (113). This pathway is activated upon a moderate cholesterol load stress and it is proposed as a protective mechanism to reduce macrophage cholesterol mass (113). Other genes involved in immune regulation are similarly altered in Tspo -/-mice (see Table 2) further validating a role for TSPO in the regulation of these processes.…”
Section: Tspo -/-Knockout Mice: New Insights Of An Old Functionmentioning
confidence: 99%
“…Transient overexpression of TSPO in human macrophages enhanced efflux of cholesterol to apoA-I, HDL, and human serum, while knockdown of TSPO achieved the reverse [153]. TSPO overexpression increased expression of ABCA1, ABCG4, and ApoE, decreased macrophage total lipid mass without induction of lipogenesis, and effectively blocked "foam cell" formation following exposure to modified LDL [153]. These effects were associated with induction of both LXR and PPAR, the latter providing a plausible explanation for the reductions in macrophage lipid mass.…”
Section: Mitochondrial Cholesterol Trafficking In Macrophagesmentioning
confidence: 93%
“…Expression of TSPO is upregulated by exposure to modified LDL in human macrophages [153] and in microglia by lipopolysaccharide (LPS) [154], and TSPO ligands have been used to image macrophage burden and intraplaque inflammation within human and murine atherosclerotic lesions [155][156][157]. Transient overexpression of TSPO in human macrophages enhanced efflux of cholesterol to apoA-I, HDL, and human serum, while knockdown of TSPO achieved the reverse [153]. TSPO overexpression increased expression of ABCA1, ABCG4, and ApoE, decreased macrophage total lipid mass without induction of lipogenesis, and effectively blocked "foam cell" formation following exposure to modified LDL [153].…”
Section: Mitochondrial Cholesterol Trafficking In Macrophagesmentioning
confidence: 99%
“…Ordinal regression was used to evaluate the degree of amyloid angiopathy using the same modeling approach and set of covariates as above. Due to their biologically related functions in cholesterol transport 69 and TSPO's ability to up-regulate APOE, 70 interactions between APOE "4 status and TSPO genotype were also tested in each model. For all analyses, P-values are two-tailed and reported as Bonferronicorrected (P cor ) or uncorrected (P raw ).…”
Section: Discussionmentioning
confidence: 99%